Attenuation of portal hypertension by natural taurine in rats with liver cirrhosis - Liang, Jian (The WJG Press and Baishideng, 2009)
AIM: To investigate the inhibitory effect of natural taurine (NTau) on portal hypertension (PHT) in rats with experimentally-induced liver cirrhosis (LC). METHODS: Experimentally-induced LC Wistar rats (20 rats/group) were treated with either oral saline or oral NTau for 6 consecutive weeks. Evaluation parameters included portal venous pressure (PVP), portal venous resistance (PVR), portal venous flow (PVF), splanchnic vascular resistance (SVR) and mean arterial pressure (MAP). Vasoactive substance levels including nitric oxide (NO), nitric oxide synthase (NOS) and cyclic guanosine monophosphate (cGMP) were also measured. Histological investigation of type I and III collagen (COL I and III) and transforming growth factor-β(1) (TGF-β1) was also performed. RESULTS: Treatment with NTau (1) significantly decreased PVP, PVR and PVF, and increased MAP and SVP; (2) markedly increased the vascular compliance and reduced the zero-stress of the portal vein; (3) markedly decreased the amount of NO and cGMP and activity of NOS; and (4) improved the pathological status of the liver tissue and reduced the expression of COL I, COL III and TGF-β1. CONCLUSION: NTau inhibited the LC-induced PHT by improving hyperdynamic circulation, morphology of liver and biomechanical properties of the portal vein in experimentally-induced LC rats.